Regulators of the G1 Phase of the Cell Cycle and Neurogenesis - Paris, Maryline; Andrisani, Ourania M. (Central Nervous System Agents in Medicinal Chemistry, 2007)
During neurogenesis, precursor cells undergo a defined number of divisions and terminally differentiate as postmitotic neurons. In the adult mammal, under certain conditions, postmitotic neurons re-enter the cell cycle and divide. The accumulated evidence demonstrates that the precise control of cell-cycle progression is critical for both neuronal development and maintenance of the neuronal phenotype. Cyclin-dependent Kinase Inhibitors (CDKIs) play the key role in this neuronal differentiation process of coordinating cell cycle exit and differentiation. Importantly, deregulation of the cell cycle leads to a variety of human neuronal diseases. In this review we discuss how regulation of neuronal progenitor proliferation and neuronal differentiation are coupled processes, based on evidence derived from the study of multiple animal models (mouse, Drosophila and Xenopus). In addition, we discuss the involvement of CDKIs in human neuronal diseases including cancers of neuronal systems, Alzheimer’s disease, and psychological disorders, and their potential as pharmacological targets.
Keywords: Cell cycle